An Empirical Study on the Mechanism of Agricultural Product Value Chains Driving Agricultural-Cultural-Tourism Collaborative Development from the Perspective of Cultural Empowerment - Chen, Zixin (Research on World Agricultural Economy, 2025)
With the transformation and upgrading of the global agricultural economy and the diversified development of consumer demands, cultural empowerment has emerged as a crucial driving force for restructuring agricultural product value chains and promoting the collaborative development of agriculture, culture, and tourism. Based on empirical data from 15 major agricultural regions in China during 2020-2024, this study employs mixed research methods to systematically analyze the operational mechanisms, influencing factors, and development effects of agricultural product value chains driving agri-cultural-tourism collaborative development from the perspective of cultural empowerment. The research constructs a theoretical analytical framework for cultural empowerment in agricultural product value chain upgrading, identifies three-level empowerment pathways including cultural resource development, cultural value transformation, and cultural brand building, and establishes a driving mechanism model for agri-cultural-tourism collaborative development. Empirical results indicate that: cultural empowerment has a significantly positive impact on agricultural product value chain upgrading, with each unit increase in cultural empowerment intensity leading to an average 23.7% improvement in agricultural product value chain efficiency and a 31.2% enhancement in product premium capability; agri-cultural-tourism collaborative development generates significant effects across economic, socio-cultural, and ecological dimensions, with comprehensive development models achieving 56.8% higher economic benefits than single models, 73.6% improvement in cultural heritage protection levels, and 82.4% enhancement in community cohesion; policy environment, market demand changes, and technological innovation constitute core driving factors for collaborative development, with policy support intensity showing significant positive correlation with development effectiveness (r=0.847), and digital technology applications improving integration efficiency by 59.7%; different development models exhibit differentiated characteristics, with comprehensive development models demonstrating optimal sustainability (92.7%), export-oriented models achieving highest economic efficiency (86.3%), and cultural tourism models showing best cultural protection effects (89.6%); culturally empowered agricultural products demonstrate strong competitive advantages in international trade, with export growth rates (38.9%) significantly higher than traditional agricultural products (12.7%) and international market premiums reaching 47.6%. This research enriches agricultural value chain theory and industrial integration theory, providing theoretical foundations and practical guidance for promoting high-quality agricultural development, rural revitalization, and enhancement of agricultural international competitiveness, with important significance for promoting global sustainable agricultural development and rural economic transformation.